Determining Competitiveness of Indonesian Export Commodities using Revealed Comparative Analysis - Suparmono, Suparmono; Suandana, Edi; Ilmas, Fauzan (Universitas Muhammadiyah Yogyakarta, 2022)
This article aims to analyze Indonesian products’ competitiveness in the global market using the static revealed comparative advantage (SRCA) and the dynamic revealed comparative advantage (DRCA). DRCA is considered superior to RCA because it takes into account the time element. The current research combines DRCA and RCA to provide an analytical comparison. The data were collected from the International Trade Centre, classified according to the Harmonized System (HS) from 2013 to 2019. Using SRCA, Indonesia’s tin and articles’ competitiveness only contributes 0.95% of Indonesia's total exports. The most significant shares of exports are mineral fuels, mineral oils, and their distillation products; bituminous substances; animal or vegetable fats and oils, and their cleavage products; and prepared edible fats. Using DRCA, Indonesia’s most significant exports in the rising star category are natural rubber and its derivatives; cars and other motorized vehicles; fatty acids and their derivatives; lignite; unforged lead; ferroalloys; wires and cables; refined copper; petroleum and minerals; and margarine and its derivatives. These products showed positive growth higher than the global average, which means Indonesia is competitive in exporting these products. Thus, the government could prioritize these products for export.